Statistical optimisation of process parameters on the efficiency of N-TiO2 dye sensitised solar cell using response surface methodology (RSM) - Samaila, Buda; Shafie, Suhaidi; Abdul Rashid, Suraya; Jaafar, Haslina; Abdgalil, Ali Khalifa (Universiti Putra Malaysia Press, 2017)
In this study, nitrogen doped titanium dioxide-based dye-sensitised solar cell was successfully fabricated using screen printing technique to discover the optimisation of process parameters for the solar cell efficiency using response surface methodology (RSM). Parameter optimisation has been a major concern in solar cell fabrication. The selected parameters were: nitrogen concentration (15-25 mg of urea), the film thickness (25-60 µm) and dye loading time (12-24 hours), the optimum condition which yields the highest efficiency of 3.5% was at 15 mg nitrogen concentration, 25 µm film thickness and 24-hours dye loading time. Film thickness was found to have a significant influence on efficiency while the loading time exceeding 18 hours has the least significant effect.